From Memorization to Meaning-Making: Rethinking Learning Outcomes in Contemporary Islamic Education - Mahmoud Abdullah; Huzaiman Hushin; Salma Begum; Yousif Mahmadov; Abdallah El-Khatib (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study explores the transformation of learning outcomes in contemporary Islamic education by examining the shift from memorization-oriented learning toward meaning-making-oriented educational practices. The purpose of the study is to analyze the theoretical foundations, educational implications, and future directions of meaningful learning within Islamic educational contexts. The research employs a qualitative library research approach through a systematic review of contemporary literature including peer-reviewed journal articles, academic books, policy reports, and educational documents. Data were analyzed using thematic content analysis to identify recurring concepts, theoretical trends, and emerging perspectives related to learning outcomes, constructivism, transformative learning, deep learning, and Islamic educational philosophy. The findings reveal that memorization remains an important foundational component of Islamic education; however, it should be integrated into broader processes of understanding (fahm), reflection (tafakkur), wisdom (ḥikmah), ethical action (‘amal), character formation (ta’dīb), and holistic development (tarbiyah). The study further demonstrates significant conceptual convergence between contemporary learning theories and classical Islamic educational principles in promoting learner agency, critical thinking, ethical reasoning, and social responsibility. The novelty of this study lies in the development of the Meaning-Making Islamic Learning Outcomes Framework (MMILOF), an integrative model that synthesizes Islamic epistemological concepts with contemporary educational theories to provide a comprehensive framework for educational reform. The study concludes that Islamic education should move beyond viewing memorization as an end goal and instead position it as a foundation for meaningful, transformative, and holistic learning.